2002
DOI: 10.1007/s00404-002-0441-1
|View full text |Cite
|
Sign up to set email alerts
|

The lipid and clinical effects of sequential transdermal estradiol and estradiol/norethisterone acetate in 674 women

Abstract: Transdermal administration of E(2) and sequential NETA for a period of 48 weeks (twelve 28-day cycles) was associated with beneficial changes, albeit of differing magnitudes, in the concentration of total cholesterol, LDL-C and triglycerides. This protective lipid profile, together with satisfactory clinical efficacy and acceptable safety and compliance, makes this system a good alternative in hormone replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 31 publications
3
4
0
Order By: Relevance
“…In the present study, all ET modalities caused a significant decline in t‐Chol levels starting from the sixth month. The results with the oral and transdermal routes are in accordance with previous reports 12–14 . However, contrary to the present results, 6 months of intranasal therapy has been reported to have no effect on t‐Chol 15 .…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, all ET modalities caused a significant decline in t‐Chol levels starting from the sixth month. The results with the oral and transdermal routes are in accordance with previous reports 12–14 . However, contrary to the present results, 6 months of intranasal therapy has been reported to have no effect on t‐Chol 15 .…”
Section: Discussionsupporting
confidence: 89%
“…25,27,29 Serum triglycerides have been found to be increased with oral and decreased with transdermal estrogen therapy. 28,29 In our present study, we observed a significant fall in TC and LDL, and an increase in HDL and TG in both the continuous combined HRT and the LycoRed group. The oxidative stress markers also showed a positive change, which was similar in both the groups.…”
Section: Discussionsupporting
confidence: 62%
“…24 Reduction in the serum TC and LDL has been reported in patients receiving unopposed or combined HRT, both by oral and parentral route. [25][26][27][28] However, the data on other lipids is less consistent with studies showing an increase, decrease or no change in HDL levels. 25,27,29 Serum triglycerides have been found to be increased with oral and decreased with transdermal estrogen therapy.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations